Enhancing Operational Risk Management in the Mauritian Banking Sector: A Structured Approach - Ramdani, Lovena; Abbana, Sharanam; Marimuthu, Ferina (International Journal of Economics and Financial Issues, 2024)
The purpose of this study aims to improve risk control, mitigation, and interbank risk comparison by advocating for Mauritian banks to adopt a standardised operational risk definition. The study suggests improving operational risk reduction or hedging, encouraging openness in risk management capabilities, and standardising risk assessment methods in accordance with Bank of Mauritius requirements. The study also recommends that banks create operational risk management committees to supervise risk control and mitigation initiatives. These committees should be composed of experienced personnel who are well-versed in the consequences of operational risk in the banking industry. Using a mixed-method approach, insights are obtained from various banks operating in Mauritius, with data acquired from a substantial sample of 150 participants. Targeting Mauritian bankers, questionnaires were distributed across reputable banks, and data were meticulously collected and analysed. The findings highlight contemporary concerns regarding economic well-being and the security of assets held by banks. It is recommended to implement changes on a modest scale initially, subject to close monitoring over a specified period, with the possibility of gradual expansion if successful outcomes ensue. In conclusion, this research is significant due to the limited exploration into operational risk management within the Mauritian context.